How to Use Crowdsourcing Effectively: Guidelines and Examples - Simperl, Elena (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
Crowdsourcing has become the mot du jour when it comes to resolving any types of problems, online or offline, that require sustained human involvement. We see it applied in order to motivate employees to engage with less rewarding daily routines, to attract the best possible ideas and approaches to boost innovation, or to complete data processing tasks that computing technology has yet to master quickly and accurately.In this paper we look at its various forms and flavors, from gamification to human computation and grand challenges, and discuss how it could be used to turn conventional content management applications into social machines in which tasks are performed as optimal combinations of human and computational intelligence. We introduce a framework for the analysis of the most important building blocks of such systems, as well as design and participation best practices that should guide their development.